2016
DOI: 10.1016/j.carbon.2015.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of structures and concentrations of carbon particle species in premixed flames by the use of in-situ wide angle X-ray scattering

Abstract: In-situ wide-angle X-ray scattering (WAXS) measurements have been conducted on atmospheric-pressure fuel-rich premixed freely propagating ethylene/oxygen flames with argon and nitrogen dilution. In this work, a novel analysis methodology able to provide quantitative information on soot/carbon particle species and concentrations was tested under heavy sooting conditions. The particle composition and concentrations were retrieved by fitting theoretical calculations of structural components from major molecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…This material showed considerable "thermal elasticity" with a density that changed by 30% between 300 and 600 K, approximately. We have also observed that flames can produce graphene/sheet-like structures either in few layers [10] or as components in the soot particles [11]. These structures are characterized by a high surface-to mass ratio, and in principle, the surface properties of the nanostructure subunits of soot particles can be changed by preparation utilizing controlled 4 (37) oxidation processes.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…This material showed considerable "thermal elasticity" with a density that changed by 30% between 300 and 600 K, approximately. We have also observed that flames can produce graphene/sheet-like structures either in few layers [10] or as components in the soot particles [11]. These structures are characterized by a high surface-to mass ratio, and in principle, the surface properties of the nanostructure subunits of soot particles can be changed by preparation utilizing controlled 4 (37) oxidation processes.…”
Section: Introductionmentioning
confidence: 79%
“…Graphitic structures with plane separation around 3.6 Å that are slightly smaller in value have been have been reported from both X-ray scattering and HRTEM on soot. Larger spaces can also be found for regions with more strand-like structures on the surface of less dense soot particles, which contain folded carbon or graphene structures with diameters that may exceed 10 Å [11]. Consequently, these may act as pockets or pores on the surface, which have a higher tendency to absorb methane at higher pressures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations